2023
DOI: 10.3390/ijerph20021116
|View full text |Cite
|
Sign up to set email alerts
|

Spillover Effects among Electricity Prices, Traditional Energy Prices and Carbon Market under Climate Risk

Abstract: With the increase in global geopolitical risks and the frequent occurrence of extreme climate in recent years, the electricity prices in Europe have shown large fluctuations. Electricity price has an important impact on the cost of production and living, while electricity demand will also affect other energy markets. A double-layer system based on the spillover effects from a systematic perspective is constructed in this paper to explore the connectedness between different electricity markets and other related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Further, they found that the risk spillover among the three is higher in the state of high volatility frequency, and geopolitical events will drive the increase of network correlation. Liu et al (2023) [25] Construct a two-tier spillover network of the electricity market, traditional energy market and carbon market in European countries to explore the impact of climate risk on network structure and nodes. They found that there are two-way spillovers between markets and that extreme events such as the Russia-Ukraine conflict can have an impact on network structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, they found that the risk spillover among the three is higher in the state of high volatility frequency, and geopolitical events will drive the increase of network correlation. Liu et al (2023) [25] Construct a two-tier spillover network of the electricity market, traditional energy market and carbon market in European countries to explore the impact of climate risk on network structure and nodes. They found that there are two-way spillovers between markets and that extreme events such as the Russia-Ukraine conflict can have an impact on network structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, Europe has become an important region for global electricity consumption, accounting for 20% of the world's total electricity consumption. However, the European region has been affected by various extreme events such as heatwaves, the Russia-Ukraine conflict, and the COVID-19 pandemic, which have had varying degrees of impact on the electricity market and consumption behavior [20,[37][38][39][40][41]. In particular, in 2022, electricity prices in Europe more than doubled, maintaining a leading position in global electricity price increases [42].…”
Section: Study Areamentioning
confidence: 99%